Neural Correlates of Social Touch Processing: An fMRI Study on Brain Functional Connectivity - Vladimir Khorev; Semen Kurkin; Larisa Mayorova; Galina Portnova; Anastasia Kushnir; Alexander Hramov (Journal of Integrative Neuroscience)
Background: The significance of tactile stimulation in human social development and personal interaction is well documented; however, the underlying cerebral processes remain under-researched. This study employed functional magnetic resonance imaging (fMRI) to investigate the neural correlates of social touch processing, with a particular focus on the functional connectivity associated with the aftereffects of touch. Methods: A total of 27 experimental subjects were recruited for the study, all of whom underwent a 5-minute calf and foot massage prior to undergoing resting-state fMRI. Additionally, 11 healthy controls participated solely in the resting-state fMRI recording. A functional connectivity network analysis was conducted to examine the alterations in connections between different brain regions following massage. Results: The findings indicated the involvement of discrete neural networks in the processing of social touch, with notable discrepancies in functional connectivity observed between the experimental and control groups. The study revealed that the control group exhibited a higher degree of connectivity within a subnetwork comprising 25 connections and 23 nodes than the experimental group following the massage intervention. The experimental group showed hypoactivation in this subnetwork following the massage. The left anterior pulvinar thalamus and the right pregenual anterior cingulate cortex, which serve as the key hubs within this subnetwork, exhibited higher clustering and increased node strength in the control group. Relatively small and unequal sample sizes are the limitations of the study that may affect the generalizability of the results. Conclusions: These findings elucidate the neural underpinnings of tactile experiences and their potential impact on behavior and emotional state. Gaining insight into these mechanisms could inform therapeutic approaches that utilize touch to mitigate stress and enhance mental health. From a practical standpoint, our results have significant implications for the development of sensory stimulation strategies for patients with prolonged disorders of consciousness, sensory loss, autism spectrum disorders, or limited access to tactile interaction in their upper extremities.